Nivel de conocimiento del impacto ambiental de plásticos de un solo uso en los alumnos del colegio Amazonas, Loreto, 2024 - Tong Navarro, Jossthin Antonio (2025)
The pollution caused by single-use plastics represents a global issue that severely affects Amazonian ecosystems and human health. This research evaluated the level of knowledge and environmental perception among students at Amazonas School, Loreto, in 2024, using a quantitative approach through surveys applied to secondary school students. The results revealed that 56.34% of students have a moderate level of knowledge with a positive trend, although technical aspects such as decomposition time and environmental regulations showed low levels of understanding. However, the perception of the negative impacts of plastics was high, especially in higher grades, where a positive correlation between knowledge and perception was observed. It is concluded that educational programs have been effective in raising environmental awareness, but it is necessary to strengthen technical content and practical strategies to promote a sustainable culture in the region.